2012
DOI: 10.3109/00365521.2012.666672
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical mucosal inflammation in diarrhea-predominant irritable bowel syndrome (IBS) in a tropical setting

Abstract: There was evidence of subclinical intestinal mucosal inflammation in patients with IBS-D. The finding of increased eosinophils is novel, and may be of special relevance to IBS-D in the tropics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 25 publications
3
35
1
Order By: Relevance
“…Loss of the protective anti‐inflammatory role of IL‐10 in the gut mucosa may potentiate susceptibility to intestinal inflammation of IBS patients . These findings are in line with another study, which had pooled samples from the terminal ileum and different segments of the colon, in which IL‐10 was significantly lower in IBS patients, compared to controls . It is important to examine the relationship between mRNA expression and the local cytokine levels, as the latter expression are better indicators of function.…”
Section: Discussionsupporting
confidence: 73%
“…Loss of the protective anti‐inflammatory role of IL‐10 in the gut mucosa may potentiate susceptibility to intestinal inflammation of IBS patients . These findings are in line with another study, which had pooled samples from the terminal ileum and different segments of the colon, in which IL‐10 was significantly lower in IBS patients, compared to controls . It is important to examine the relationship between mRNA expression and the local cytokine levels, as the latter expression are better indicators of function.…”
Section: Discussionsupporting
confidence: 73%
“…In all, 66 articles were identified that provided results on either mucosal or serological immune markers in IBS; 43 reported on mucosal changes, 19 on serological markers and seven on both. Some focused on specific IBS subtypes, including three reported on a comparison of diarrhea‐predominant IBS (IBS‐D) with healthy controls, one compared post‐infection (PI)‐IBS to the general population, and three limited their evaluation to a comparison between PI‐IBS and IBS‐D . In other studies, abnormal findings were limited to certain IBS subtypes; one study linked IL‐1β with constipation‐predominant IBS (IBS‐C) and IL‐6 and TNF‐α with IBS‐D; another also associated elevated serum levels of TNF‐α and IL‐6 with IBS‐D and five studies showed that abnormalities in mucosal immune markers were confined to certain IBS subtypes: IBS‐D alone in comparison to all other subtypes in five studies, and IBS‐D and mixed IBS (IBS‐M) in comparison to IBS‐C and healthy controls in one …”
Section: Resultsmentioning
confidence: 99%
“…When analyzing data on mast cells in IBS, we should consider that these cells share many characteristics with eosinophils and basophils. The evidence for involvement of eosinophils and basophils in IBS is not as extensive as mast cells . Therefore, future studies should also consider evaluating the roles of eosinophils and basophils, as well as the cross talk among these immune cells in the pathophysiology of IBS.…”
Section: Discussionmentioning
confidence: 99%